Seismic Monitoring of a Subarctic River: Seasonal Variations in Hydraulics, Sediment Transport, and Ice Dynamics. Issue 7 (23rd July 2020) - Polvi, L. E.; Dietze, M.; Lotsari, E.; Turowski, J. M.; Lind, L.
Abstract: High‐latitude rivers are commonly covered by ice for up to one third of the year. Our understanding of the effects of ice on channel morphodynamics and bedload transport is hindered by the difficulties of sensing through the ice and dangers of field work on thin ice or during ice break‐up. To avoid this drawback, we used seismic signals to interpret processes and quantify water and sediment fluxes. Our objective was to determine seasonal differences in hydraulics and bedload sediment transport under ice‐covered versus open‐channel flow conditions using a small seismic network and to provide a first‐order estimation of sediment flux in a Fennoscandian river. Our study reach was on a straight, low‐gradient section of the Sävar River in northern Sweden. Interpretations of seismic signals, from a station 40 m away from the river, and inverted physical models of river stage and bedload flux indicate clear seasonal differences between ice‐covered and open‐channel flow conditions. Diurnal cycles in seismic signals reflecting turbulence and sediment transport are evident directly after ice break‐up. Analysis of seismic signals of ice‐cracking support our visual interpretation of ice break‐up timing and the main ice break‐up mechanism as thermal rather than mechanical. Assuming the bulk of sediment moves during ice break‐up and the snowmelt flood, we calculate a minimum annual sediment flux of 56.2 ± 0.7 t/km 2, which drastically reduces the uncertainty from previous estimates (0–50 t/km 2 ) that exclude ice‐covered or ice break‐up periods. Plain Language Summary: With changing ice dynamics under climate change, we must understand how river dynamics including sediment flux differ under ice‐covered versus open‐channel flow conditions and during ice break‐up. However, it is nearly impossible to study sediment transport using common techniques, as we cannot see geomorphic processes below the ice. Field measurements are dangerous to carry out on unstable ice and during ice‐break up, which may be the most dynamic period for sediment transport and bank erosion. To overcome this problem, we employed a relatively new approach of environmental seismology to collect continuous data on instream processes. We measured ice dynamics and break‐up along the Sävar River in northern Sweden and found distinct differences in water flow patterns and sediment transport between ice‐covered and open‐channel flow conditions. Seismic signals of ice cracking agree with visual observations that ice break‐up was due to ice slowly melting instead of more sudden mechanical fracturing. We also calculated a minimum annual sediment flux of ~55 t/km 2 —one of the first for this region and for ice‐covered rivers—that is much more precise than previous estimates (0–50 t/km 2 ) without ice‐covered or ice break‐up periods. Key Points: Modeled flow stage and bedload flux from seismic signal inversions show seasonal and diurnal differences in an ice‐covered subarctic river Ice break‐up mechanism (thermal or mechanical) was determined from rate and timing of seismic ice‐cracking signals We seismically modeled a sediment flux of 56.2 ± 0.7 t/km 2 /a, which reduces previous uncertainty ranges (0–50 t/km 2 /a) in Fennoscandia